The role of the tubular biomarkers NAG, kidney injury molecule-1 and neutrophil gelatinase-associated lipocalin in patients with chest pain before contrast media exposition. (28th March 2019) - Schlossbauer, Michael H; Hubauer, Ute; Stadler, Stefan; Hupf, Julian; Sag, Sabine; Birner, Christoph; Zimmermann, Markus; Orso, Evelyn; Fischer, Marcus; Luchner, Andreas; Maier, Lars S; Jungbauer, Carsten G
Aim: We evaluated the role of the tubular biomarkers N-acetyl-ß-D-glucosaminidase (NAG), kidney injury molecule-1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL) in patients with chest pain.Methods: Serum and urine samples were collected of 223 patients and 47 healthy controls. None of them was exposed to contrast media.Results: NAG showed among others significant correlation with N-terminal pro brain natriuretic peptide (NTproBNP), troponin I and creatinine. KIM-1 and NGAL showed weaker correlations. NAG was significantly elevated in all subgroups of acute coronary syndrome (ACS) compared with chest wall syndrome and controls. NAG was an independent predictor for the diagnosis of myocardial infarction.Conclusion: NAG may demonstrate the presence of acute tubular injury due to cardiac impairment already in the emergency department. NAG should be evaluated as marker of acute cardiorenal syndrome in patients with chest pain.